Speeding Up Chemisorption Analysis by Direct IR-Heat-Release Measurements (Infrasorp Technology): A Screening Alternative to Breakthrough Measurements - Sandra, Fabien; Klein, Nicole; Leistner, Matthias; Lohe, Martin R.; Benusch, Matthias; Woellner, Michelle; Grothe, Julia; Kaskel, Stefan (Industrial & Engineering Chemistry Research, 2015)
In this study, a new innovative adsorption screening method, Infrasorp technology, is presented as a quick and efficient measurement tool for the determination of H2S adsorption capacity and compared to breakthrough measurements. Using zinc oxide nanoparticles and metal-organic framework materials, a clear correlation between those two techniques was found, showing the broad applicability of the method for different classes of materials and the potential of Infrasorp to be used as an alternative or preliminary analysis to breakthrough measurements. This tool saves time and costs and speeds up characterization of new materials thanks to the feasibility of a quick and easy wide screening using a small amount of adsorbent.
CRIS-Team Scopus Importer:2023-03-20